Antibacterial activity of aqueous and methanol extracts of selected basidiomycetes from UPV, Miagao, Iloilo, Philippines. - Ambubuyog, Marja Victoria (2013.)
The Basidiomycetes represent an enormous source for natural products with diverse chemical structures and wide ranging antimicrobial activity. This study was done to investigate the antibacterial property of selected species of basidiomycetes aqueous and methanolic extracts against Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa. Specifically, it aimed to (1) determine the antibacterial activity of the aqueous extract of selected species of basidiomycetes in inhibiting the growth of Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa based on the zone of inhibition; (2) determine the antibacterial activity of the methanolic extract of selected species of basidiomycetes in inhibiting the growth of Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa based on the zone of inhibition; and (3) compare the aqueous and methanolic extracts of selected species of basidiomycetes in inhibiting the growth of Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa based on the zone of inhibition. A total number of ten species were collected namely Auricularia sp., Schizophyllum sp., Trametes pubescens, Trametes versicolor, Trametes elegans, Ganoderma sp.(1), Ganoderma sp.(2), Stereum sp. and two unknowns. Dried samples were crushed and extracted with water and methanol. Antibacterial activity was determined using the Kirby-Bauer disc diffusion method. The results showed a negative to weak inhibition against the test microorganisms which is inconsistent with the results of previous studies. it could possibly be attributed to the preparation of the samples and the fruiting maturity that influenced the antibacterial potential of the samples. It appears that fruiting bodies used in the present study may not be reliable sources of bioactive compounds for antibacterial activity.
Special Problem (Undergraduate, Bachelor of Science in Biology) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo
Keywords: Basidiometes -- Methanol extracts; Basidiometes -- Aqueous axtracts